Teoria histórico-cultural e suas implicações na atuação do professor de educação física escolar - Tuim Viotto Filho, Irineu Aliprando [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
This article presents a theoretical search and aims to introduce the main categories of historical-cultural theory and discuss its implications for the physical education teacher's work inside the school and also emphasizes this theory and its methodological proposal as an important way to build the scholar physical education in a critical perspective aiming to change the school and the students conscious and personality. The Vigotskian school of human development it is taken as an important reference to understand the scholars in their vital process of development and helps the teachers in general, and physical education teachers in specific, to consider the activity ( vital activity) as important instrument to get the humanization and liberty of human being, inside the school and inside the contemporary society.

Esse artigo apresenta o resultado de uma pesquisa de natureza teórica e tem objetivo de introduzir as principais categorias da teoria histórico-cultural e discutir suas implicações para o trabalho do professor de educação física escolar. Também enfatiza essa teoria e suas propostas metodológicas, como um importante caminho para se construir a educação física escolar numa perspectiva crítica e voltada à transformação qualitativa da escola e da consciência e personalidade dos estudantes. A escola vigotskiana de desenvolvimento humano é tomada como uma importante referência para se entender os estudantes no seu processo de desenvolvimento vital e pode ajudar os professores em geral e os professores de educação física em específico, a considerar a atividade (atividade vital) como importante instrumento de humanização e liberdade humana no interior da escola e no interior da sociedade contemporânea.
Historical-cultural theory and its implications on the scholar physical educations teacher's work
Keywords: Historic-cultural theory; Vigotskian school of development; Vital activity in physical education